Avanços na compreensão da subjetividade no Behaviorismo Radical - Pompermaier, Henrique Mesquita (2013)
This work aims to present and discuss different positions placed in the current debates on approach subjective phenomena in radical behaviorism. On this, the work focuses on the writings of researchers in the field of behavior analysis in the theme of subjectivity, leading to a discussion of the concepts, the role and relevance of the theory of private events for the explanation of behavior. Despite being one of the most recurrent behavior analytic treatment of this theme, the defense of the theory and concept of private events as well as the linking privacy-subjectivity, has not been developed in a consensual way. Thus, the area appears to be facing not only the challenge of establishing a clearer understanding regarding the possibility of a scientific approach to private events, but also of evaluating the coherence and relevance of this concept with the theoreticalphilosophical project of radical behaviorism. From the analysis and discussions developed, it is possible to indicate two distinct directions regarding the advances proposed for the comprehension of subjective phenomena in radical behaviorism: one relates to the refinement of the private events concept, emphasizing its relational and contextual character a circumstantially restricted observability. Another direction is built upon critical positions about the privacy notion, defending the abandonment of the theory and concept of private events in favor of an alternative approach grounded in a relational and immanent metaphysics, and understanding subjective phenomena in a continuum of complexity, referent to the interweaving of repertoires from different levels of selection.